Transforming play. (2nd May 2023) - Grimmer, Tamsin
Abstract : Early years consultant and trainer, Tamsin Grimmer, discusses ways to encourage different types of transforming play, allowing children to explore and build an understanding of scientific concepts and processes at an early age. Transforming – children like to explore and see changes, e.g. adding colour to cornflour, mixing paints together, making or manipulating play dough, adding juice to food to see what happens, adding water to sand and/or making sand moulds.